Mitochondria: promising organelle targets for cancer diagnosis and treatment. (5th September 2018) - Hou, Xiao-Shuang; Wang, Huai-Song; Mugaka, Benson Peter; Yang, Gong-Jun; Ding, Ya
Abstract : Mitochondrial-mediated tumor monitoring provides a new perspective on mitochondria-based therapy. Abstract : Mitochondria, the energy supply factories for cell-life activities, play important roles in controlling epigenetics, differentiation and initiation, and the execution of apoptosis. These functions of the mitochondria contribute to cell adaptation to challenging microenvironment conditions. In past decades, mitochondrial malfunction has been revealed to be closely related to the occurrence and development of a variety of human disorders, including cancer and multiple neurodegenerative diseases. The disturbance of the mitochondrial genome (mtDNA) or mitochondrial vital functions, e.g., the production of adenosine triphosphate (ATP) and the generation of reactive oxygen species (ROS), can potentially be involved in disease pathogenesis. Recent research has shown that the precise monitoring of mitochondrial environments can provide potential directions for cancer diagnosis. Furthermore, mitochondrial-targeted cancer treatment exhibits unparalleled superiority for enhanced tumor therapy. Therefore, in this review, we focus on mitochondrial-based cancer diagnosis via monitoring mitochondrial respiration or mitophagy. Current approaches using mitochondrial-based cancer treatments, including targeting mitochondrial ATP, mitochondrial membrane permeability, and mitochondrial ROS levels and mtDNA, are also summarized. This review will provide insights into mitochondrial-mediated tumor monitoring and mitochondrial-based therapy.